LA POLITICA ES UN JUEGO: UN ANALISIS DE LA METÁFORA POLÍTICA EN LA PRENSA ESPAÑOLA - Al. Amar, Abdullah (European Scientific Journal, ESJ, 2014)
The main objective of this paper is to analyze the political metaphor in the current Spanish news discourse .The theoretical foundations of the analysis are developed within the framework of the cognitive linguistic focus, with special emphasis on the work of Lakoff and Johnson (Metaphors of daily life 1980) and Cuenca and Hilferty (Introduction to Cognitive Linguistics 2009). After presenting the importance of using metaphor in political discourse, I have discussed in detail the metaphorical features in general and in politics in specific. Based on their nature, the mechanism to understand and analyze metaphors in political discourse may be more difficult than we think. Regarding the argumentative functions of metaphor, I have chosen the cognitive function mode analysis in different journalistic contexts. According to Felix Rodriguez, the political metaphor was used in all areas of daily life. However, to reach my purpose of analysis, I have chosen the field of play as one of the most metaphorical fields used in Spanish press, from 1977 until 1988.The quotes selected are samples of the major Spanish newspapers (Opinión, el cambio, el País, Que, etc..). Having started with the conceptual metaphor analysis, I have established a series of orientations on the origin of each metaphor and its various objectives. Finally, I have tried to explain the ontological and epistemological relations of some metaphorical expressions, using conceptual metaphors as the basis for analysis.